The Influence of Leadership and External Environment on Performance through Learning Organization, and the Influence towards Competitiveness through Performance of Institute of Economic Science in Java - Budiyono, Budiyono; Budiyanto, Budiyanto; Suwitho, Suwitho (International Review of Management and Marketing, 2018)
This study aims to provide information on how to improve the performance and competitiveness of STIE in Indonesia. The variables in this study consisted of two exogenous variables, namely leadership and the external environment. Three endogenous variables, i.e. organizational learning, performance and competitive. The method in this study uses SEM and the data processed by using Amos during the research period of five (5) months, from May 2017 to October 2017. The population in this study are Institute Of Economic Science in Java, amounting to 142 are Institute of Economic Science in Coordination of Private Universities (Kopertis) Region III to Region VII by reason of the island of Java is a barometer of higher education in Indonesia. The research result shows that the leadership has significant effect on the competitiveness of Institute of Economic Science, the external environment has a significant effect on the competitiveness of Institute of Economic Science, leadership has a significant effect on performance through organizational learning, the external environment has a significant effect on performance through organizational learning, leadership has a significant effect on competitiveness through performance, and the external environment has a significant effect on competitiveness through performance. Keywords: Leadership, external environment, organizational learning, performance and competitiveness. JEL Classifications: D83, L2